Occurrence of Aeromonas spp. Resistant to Some Selected Antibiotics Isolated from Farmed Clarias gariepinus - Deborah Arimie Adah; Lawal Sa'idu; Sonnie Joshua Oniye; Moshood Abiola Raji; Adakole Sylavnus Adah (Journal of Applied Veterinary Science And Technology, 2023)
Background: One of the major causes of disease in Clarias gariepinus is Aeromonas spp. which has been linked to significant economic losses and poses a risk to public health. Purpose: The prevalence and heterogeneity of Aeromonas species isolated from Clarias gariepinus cultured in concrete tanks, as well as the antibiogram and multiple antibiotic resistance index, were examined. Methods: In this study, using culture, biochemical characterization, and Microbact 24E kit, Aeromonas species isolates were confirmed. The Kirby Bauer disc diffusion method assessed the antibiotic susceptibility to 10 different antibiotics. Results: Four different species of Aeromonas were identified, with an overall prevalence of 55 (28.6%). Aeromonas hydrophila had the highest prevalence of 35 (18.6%), followed by 10 (5.2%) for Aeromonas caviae, then 5 (2.6 %) for Aeromonas veronii biovar sobria, and Aeromonas veronii biovar veronii, respectively. The Aeromonas species exhibited high resistance to amoxicillin, ampicillin, colistin sulphate, oxytetracycline, trimethoprim/sulphamethoxazole, and penicillin, with varied patterns of resistance, and the multiple antibiotic resistance (MAR) index values ranged between 0.10 and 0.80. Conclusion: Several antibiotic-resistant Aeromonas species were linked to the widespread emergence of antimicrobial resistance. As a result, it is crucial to regulate the use of antibiotics in fish farms and to ensure that biosecurity and preventive management strategies are applied effectively.